Analysis of the Role of Customs in the Effectiveness of Dwelling Time Implementation in Export-Import Activities (Study on KPPBC Belawan Medan Middle Type Customs) - Laura Adelia Mutiara Sihaloho; Ahmad Rahman Hamdani Lubis; Khairani Alawitah Matondang (PT FORMOSA CENDEKIA GLOBAL, 2023)
Dwelling Time is one of the problems faced in the implementation of export-import activities. Dwelling Time acceleration correlates with reduced logistics costs in international trade. In relation to Dwelling Time, the customs agency which in Indonesia is known as Customs has an important role in procedural and supervisory matters. Customs agencies in carrying out their duties certainly face various obstacles and an appropriate strategy is needed to overcome these obstacles so that Dwelling Time can be reduced. Tanjung Perak Port is one of the busiest ports in Indonesia.